Comparison of State and Private Universities in Turkiye in terms of Instruction and R& D Regarding the Reports of the Turkish Council of Higher Education (YÖK) - Gürbüz, Murat (PROFESSIONAL STUDIES: Theory And Practice, 2023)
Turkiye Turkish Council of Higher Education (YÖK) started to publish University Monitoring and Evaluation General Reports since 2019. Three reports (2019-2020-2021) have been published. Average annual data of state and private universities in Turkey are available in these reports. These reports also include data about various aspects of university education under the titles of Instruction and Research & Development (R&D). This study aims to determine pros and cons of state and private universities for Turkish and international university applicants by comparing the data averages of the 2019, 2020 and 2021 reports about the Instruction and the Research & Development (R&D) of both university types. Under the Instruction title; data about number of accredited undergraduate programs, occupancy rate of the programs, number of students participating in teknokent (technopole) or technology transfer office (TTO) projects, number of programs in the top 5% of the public servant selection exam (KPSS), number of international symposiums, congresses or artistic exhibitions, number of social responsibility projects implemented by students, number of industrial projects implemented by students and number of printed books and e-publications for each student were examined. Under the Research & Development title; data about number of publications published in national peer-reviewed journals and in SCI, SCI-Expanded, SSCI and AHCI indexed journals, number of cited publications in the top 10%, number of applied and granted patents, utility models and designs, number of R&D projects supported by national and international institutions and organizations, ratio of investment budget spent on R&D, income except for subsidy, innovation and product development income from laboratory services within the scope of R&D and number of joint projects with industry were examined. Document analysis method was used in the study as a qualitative research method. Document analysis includes the analysis of written materials containing information about the phenomenon or facts to be investigated. In the field of education: Textbooks, instructional regulations, internal and external correspondence, official documents... can be used as data source (Yıldırım and Şimşek, 2013, pp.217-218). Data averages of state and private universities were evaluated. Data differences among universities in same category were not included. The results shows that both state and private universities have pros and cons in terms of instruction and R&D, but state universities are advantageous regarding data numbers and diversity. While private universities are profit-oriented and attach importance to individual development, state universities are more collaborative and are community-oriented.